THE EFFECT OF BRAINSTORMING METHOD ON THE STUDENTS ABILITY IN WRITING EXPOSITION TEXT AT GRADE XI SMK SWASTA TAMANSISWA SUKADAMAI 2021/2022 - Hamidah Sidabalok, Zunaida Sitorus, Apriliana Wahyu (JURNAL PIONIR, 2022)
This study aims at investigating the effect of Brainstorming Method in writing exposition text. This study was conducted by experimental research. The sample of this study was the students at grade XI Ak and XI RPL of SMK Swasta Tamansiswa Sukadamai. The total number of the population was seventy eight students in four class. There were 41 students chosen as the sample by using random sampling technique. The sample was divided into two groups, namely control group and experimental group. The experimental group was taught by using Brainstorming Method and control group was taught without using Brainstorming Method. The instrument for collecting the data was writing test. The data was analyzed by using t-test formula. The result of the analysis shows that ttest value is higher than ttable (4,072>1,684) at level of significance 0.05 with the degree of freedom 39. It means that the alternative hypothesis (Ha) is accepted and null hypothesis (H0) is rejected. Based on the findings of this study, it was found that there is a significant effect of Brainstorming Method in writing exposition text. Key Words: Brainstorming Method, Writing, Exposition Text.